2021
DOI: 10.1111/ele.13695
|View full text |Cite
|
Sign up to set email alerts
|

Beyond nitrogen: phosphorus – estimating the minimum niche dimensionality for resource competition between phytoplankton

Abstract: The niche dimensionality required for coexistence is often discussed in terms of the number of limiting resources. N and P limitation are benchmarks for studying phytoplankton interactions. However, it is generally agreed that limitation by small numbers of resources cannot explain the high phytoplankton diversity observed in nature. Here, we parameterised resource competition models using experimental data for six phytoplankton species grown in monoculture with nine potential limiting resources. We tested pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Macronutrient E:P was relatively conserved across isolates (except for S:P), with differences in micronutrient E:P primarily responsible for isolate-specific elementomes (for both E:P and absolute data), a phenomenon documented for other marine algae [ 21 , 22 ]. There is generally less storage capacity for micronutrients making changes in stoichiometry more identifiable and our observations support recent suggestions that expansion beyond C:N:P is required to resolve a species’ biogeochemical niche [ 53 ]. Some isolates, such as CCMP2464 had large variability in elementomes between biological replicates.…”
Section: Discussionsupporting
confidence: 86%
“…Macronutrient E:P was relatively conserved across isolates (except for S:P), with differences in micronutrient E:P primarily responsible for isolate-specific elementomes (for both E:P and absolute data), a phenomenon documented for other marine algae [ 21 , 22 ]. There is generally less storage capacity for micronutrients making changes in stoichiometry more identifiable and our observations support recent suggestions that expansion beyond C:N:P is required to resolve a species’ biogeochemical niche [ 53 ]. Some isolates, such as CCMP2464 had large variability in elementomes between biological replicates.…”
Section: Discussionsupporting
confidence: 86%
“…However, the grouping of species differed depending on whether macronutrients or micronutrients and trace elements were used, suggesting a weak or non-existent relationship between both groups of elements across species. This result further indicates that each element may provide unique information regarding the functioning of the organisms and, therefore, studies using only macronutrients such as C, N, and P may be missing an important set of features of the organisms under study, as suggested by several authors [ 18 , 38 ].…”
Section: Discussionmentioning
confidence: 88%
“…Understanding ionome-wide shifts in NUEs should have important ecological and evolutionary implications, because it represents a change in the biogeochemical niche [29]. While much remains to be understood about the ecological relevance of ionomes [27,34,59], we do know that differences in the NUE of multiple elements impact trophic transfer (e.g. [35]), and can alter the geochemical environment for subsequent generations (e.g.…”
Section: Discussionmentioning
confidence: 99%